Hairdresser - Waller T; South Africa; Nafte Debbie
An introduction to the job of Hairdresser, describing the work of a hairdresser, the skills and personal qualities required, school subjects that are helpful, and the training and opportunities that are available. the book can help learners to decide if this is suitable career for them.
Juniour Non-Fiction -; Juvenile Literature